Solar System Learning Innovation through Augmented Reality: Increasing Student Concept Solar System - Ramadhani, Anggi; Ismet, Ismet; Wiyono, Ketang (Integrated Science Education Journal, 2026)
Purpose of the study: Students’ conceptual understanding of Solar System topics remains low due to the abstract nature of astronomical phenomena and the limited use of interactive visual learning media. This study aims to develop AR-based Solar System learning media that are valid, practical, and effective in improving students’ conceptual mastery. Methodology: The research employed a Research and Development approach using the 4D model. Participants comprised 46 eighth-grade students from Muhammadiyah 1 Junior High School in Palembang, selected through purposive sampling. Data collection involved teacher interviews, expert validation (3 experts), student practicality questionnaires (9 students) and pretest-posttest assessments (46 respondents),. The instruments included closed-ended Likert-scale items, open-ended feedback, and concept mastery tests. Data analysis was conducted using the Guttman scale for validity, the Likert scale for practicality, and the N-gain test for effectiveness. Main Findings: The developed AR learning media achieved a validity score of 100%, a practicality score of 96.82% (very practical), and high effectiveness, with an average N-gain of 0.71. Students’ posttest scores showed substantial improvement compared to pretest results, indicating enhanced understanding of planetary motion, rotation, and revolution. Novelty/Originality of this study: The findings confirm that AR-based learning media effectively facilitate conceptual change by transforming abstract Solar System concepts into concrete, interactive experiences. The novelty of this study lies in integrating realistic 3D visualization, curriculum-oriented design, and effectiveness testing. The results imply that AR media can serve as a viable instructional innovation in science education, particularly for abstract topics that require spatial reasoning.